Reviewing the Tannic Acid Mediated Synthesis of Metal Nanoparticles - Tufail Ahmad (Journal of Nanotechnology)
Metal nanoparticles harbour numerous exceptional physiochemical properties absolutely different from those of bulk metal as a function of their extremely small size and large superficial area to volume. Naked metal nanoparticles are synthesized by various physical and chemical methods. Chemical methods involving metal salt reduction in solution enjoy an extra edge over other protocols owing to their relative facileness and capability of controlling particle size along with the attribute of surface tailoring. Although chemical methods are the easiest, they are marred by the use of hazardous chemicals such as borohydrides. This has led to inclination of scientific community towards eco-friendly agents for the reduction of metal salts to form nanoparticles. Tannic acid, a plant derived polyphenolic compound, is one such agent which embodies characteristics of being harmless and environmentally friendly combined with being a good reducing and stabilizing agent. In this review, first various methods used to prepare metal nanoparticles are highlighted and further tannic acid mediated synthesis of metal nanoparticles is emphasized. This review brings forth the most recent findings on this issue.